Human–AI Collaboration as a Strategic Capability in the Creative Economy - Reny Sumarni (UDEX Institute, 2026)
The rapid advancement of artificial intelligence (AI), particularly generative systems, has transformed its role from a supportive tool into an active participant in organizational processes, especially within the creative economy where value creation is increasingly co-produced. Despite this shift, existing literature remains fragmented across strategic management, AI capability, and human–AI interaction, lacking an integrated framework that explains how human–AI collaboration systematically drives value creation. This study aims to conceptualize human–AI collaboration as a firm-level strategic capability by addressing this theoretical gap. Adopting a conceptual and integrative approach, the study synthesizes insights from dynamic capabilities, AI capability research, and creativity and innovation literature to develop a multidimensional framework. The proposed model conceptualizes Human–AI Collaboration Capability (HACC.) as comprising cognitive augmentation, generative co-creation, adaptive orchestration, and value attribution capability, operating through an iterative collaboration cycle that links micro-level interaction processes to macro-level strategic outcomes. The study contributes by extending capability theory toward distributed cognition and hybrid agency, offering a process-oriented explanation of value creation, and providing a foundation for future empirical research in AI-enabled organizational contexts.